Design aspects of Bi2Sr2CaCu2O8+δ THz sources: optimization of thermal and radiative properties - Krasnov, Mikhail M.; Novikova, Natalia D.; Cattaneo, Roger; Kalenyuk, Alexey A.; Krasnov, Vladimir M. (Beilstein Journal of Nanotechnology, 2021)
Impedance matching and heat management are important factors influencing the performance of terahertz sources. In this work we analyze thermal and radiative properties of such devices based on mesa structures of a layered high-temperature superconductor Bi2Sr2CaCu2O8+δ. Two types of devices are considered containing either a conventional large single crystal or a whisker. We perform numerical simulations for various geometrical configurations and parameters and make a comparison with experimental data for the two types of devices. It is demonstrated that the structure and the geometry of both the superconductor and the electrodes play important roles. In crystal-based devices an overlap between the crystal and the electrode leads to appearance of a large parasitic capacitance, which shunts terahertz emission and prevents impedance matching with open space. The overlap is avoided in whisker-based devices. Furthermore, the whisker and the electrodes form a turnstile (crossed-dipole) antenna facilitating good impedance matching. This leads to more than an order of magnitude enhancement of the radiation power efficiency in whisker-based, compared to crystal-based, devices. These results are in good agreement with presented experimental data.
Keywords: high-temperature superconductivity; Josephson junctions; numerical modelling; terahertz sources

(untitled) - Tonouchi, M. (Nat. Photonics, 2007)

(untitled) - Razeghi, M.; Lu, Q. Y.; Bandyopadhyay, N.; Zhou, W.; Heydari, D.; Bai, Y.; Slivken, S. (Opt. Express, 2015)

(untitled) - Belkin, M. A.; Capasso, F. (Phys. Scr., 2015)

(untitled) - Wang, X.; Shen, C.; Jiang, T.; Zhan, Z.; Deng, Q.; Li, W.; Wu, W.; Yang, N.; Chu, W.; Duan, S. (AIP Adv., 2016)

(untitled) - Curwen, C. A.; Reno, J. L.; Williams, B. S. (Nat. Photonics, 2019)

(untitled) - Walther, C.; Fischer, M.; Scalari, G.; Terazzi, R.; Hoyler, N.; Faist, J. (Appl. Phys. Lett., 2007)

(untitled) - Vijayraghavan, K.; Jiang, Y.; Jang, M.; Jiang, A.; Choutagunta, K.; Vizbaras, A.; Demmerle, F.; Boehm, G.; Amann, M. C.; Belkin, M. A. (Nat. Commun., 2013)

(untitled) - Rösch, M.; Scalari, G.; Beck, M.; Faist, J. (Nat. Photonics, 2015)

(untitled) - Ozyuzer, L.; Koshelev, A. E.; Kurter, C.; Gopalsami, N.; Li, Q.; Tachiki, M.; Kadowaki, K.; Yamamoto, T.; Minami, H.; Yamaguchi, H.; Tachiki, T.; Gray, K. E.; et al. (Science, 2007)

(untitled) - Benseman, T. M.; Gray, K. E.; Koshelev, A. E.; Kwok, W.-K.; Welp, U.; Minami, H.; Kadowaki, K.; Yamamoto, T. (Appl. Phys. Lett., 2013)

(untitled) - Welp, U.; Kadowaki, K.; Kleiner, R. (Nat. Photonics, 2013)

(untitled) - Kashiwagi, T.; Yamamoto, T.; Minami, H.; Tsujimoto, M.; Yoshizaki, R.; Delfanazari, K.; Kitamura, T.; Watanabe, C.; Nakade, K.; Yasui, T.; Asanuma, K.; Saiwai, Y.; et al. (Phys. Rev. Appl., 2015)

(untitled) - Zhou, X.; Zhu, Q.; Ji, M.; An, D.; Hao, L.; Sun, H.; Ishida, S.; Rudau, F.; Wieland, R.; Li, J.; Koelle, D.; Eisaki, H.; et al. (Appl. Phys. Lett., 2015)

(untitled) - Borodianskyi, E. A.; Krasnov, V. M. (Nat. Commun., 2017)

(untitled) - Sun, H.; Wieland, R.; Xu, Z.; Qi, Z.; Lv, Y.; Huang, Y.; Zhang, H.; Zhou, X.; Li, J.; Wang, Y.; Rudau, F.; Hampp, J. S.; et al. (Phys. Rev. Appl., 2018)

(untitled) - Kashiwagi, T.; Yuasa, T.; Tanabe, Y.; Imai, T.; Kuwano, G.; Ota, R.; Nakamura, K.; Ono, Y.; Kaneko, Y.; Tsujimoto, M.; Minami, H.; Yamamoto, T.; et al. (J. Appl. Phys., 2018)

(untitled) - Zhang, H.; Wieland, R.; Chen, W.; Kizilaslan, O.; Ishida, S.; Han, C.; Tian, W.; Xu, Z.; Qi, Z.; Qing, T.; Lv, Y.; Zhou, X.; et al. (Phys. Rev. Appl., 2019)

(untitled) - Kuwano, G.; Tsujimoto, M.; Kaneko, Y.; Imai, T.; Ono, Y.; Nakagawa, S.; Kusunose, S.; Minami, H.; Kashiwagi, T.; Kadowaki, K.; Simsek, Y.; Welp, U.; et al. (Phys. Rev. Appl., 2020)

(untitled) - Tsujimoto, M.; Fujita, S.; Kuwano, G.; Maeda, K.; Elarabi, A.; Hawecker, J.; Tignon, J.; Mangeney, J.; Dhillon, S. S.; Kakeya, I. (Phys. Rev. Appl., 2020)

(untitled) - Saiwai, Y.; Kashiwagi, T.; Nakade, K.; Tsujimoto, M.; Minami, H.; Klemm, R. A.; Kadowaki, K. (Jpn. J. Appl. Phys., 2020)

(untitled) - Delfanazari, K.; Klemm, R. A.; Joyce, H. J.; Ritchie, D. A.; Kadowaki, K. (Proc. IEEE, 2020)

(untitled) - Saito, Y.; Adachi, S.; Matsumoto, R.; Nagao, M.; Fujita, S.; Hayama, K.; Terashima, K.; Takeya, H.; Kakeya, I.; Takano, Y. (Appl. Phys. Express, 2021)

(untitled) - Kleiner, R.; Müller, P. (Phys. Rev. B, 1994)

(untitled) - Krasnov, V. M.; Mros, N.; Yurgens, A.; Winkler, D. (Phys. Rev. B, 1999)

(untitled) - Katterwe, S. O.; Krasnov, V. M. (Phys. Rev. B, 2009)

(untitled) - Katterwe, S. O.; Rydh, A.; Motzkau, H.; Kulakov, A. B.; Krasnov, V. M. (Phys. Rev. B, 2010)

(untitled) - Krasnov, V. M.; Yurgens, A.; Winkler, D.; Delsing, P.; Claeson, T. (Phys. Rev. Lett., 2000)

(untitled) - Krasnov, V. M. (Phys. Rev. B, 2009)

(untitled) - Krasnov, V. M.; Yurgens, A.; Winkler, D.; Delsing, P. (J. Appl. Phys., 2001)

(untitled) - Krasnov, V. M. (Phys. C (Amsterdam, Neth.), 2002)

(untitled) - Krasnov, V. M.; Sandberg, M.; Zogaj, I. (Phys. Rev. Lett., 2005)

(untitled) - Yurgens, A. (Phys. Rev. B, 2011)

(untitled) - Kakeya, I.; Omukai, Y.; Yamamoto, T.; Kadowaki, K.; Suzuki, M. (Appl. Phys. Lett., 2012)

(untitled) - Tsujimoto, M.; Kambara, H.; Maeda, Y.; Yoshioka, Y.; Nakagawa, Y.; Kakeya, I. (Phys. Rev. Appl., 2014)

(untitled) - Asai, H.; Kawabata, S. (Appl. Phys. Lett., 2014)

(untitled) - Rudau, F.; Tsujimoto, M.; Gross, B.; Judd, T. E.; Wieland, R.; Goldobin, E.; Kinev, N.; Yuan, J.; Huang, Y.; Ji, M.; Zhou, X. J.; An, D. Y.; et al. (Phys. Rev. B, 2015)

(untitled) - Benseman, T. M.; Koshelev, A. E.; Vlasko-Vlasov, V.; Hao, Y.; Kwok, W.-K.; Welp, U.; Keiser, C.; Gross, B.; Lange, M.; Kölle, D.; Kleiner, R.; Minami, H.; et al. (Phys. Rev. Appl., 2015)

(untitled) - Rudau, F.; Wieland, R.; Langer, J.; Zhou, X. J.; Ji, M.; Kinev, N.; Hao, L. Y.; Huang, Y.; Li, J.; Wu, P. H.; Hatano, T.; Koshelets, V. P.; et al. (Phys. Rev. Appl., 2016)

(untitled) - Oikawa, D.; Mitarai, H.; Tanaka, H.; Tsuzuki, K.; Kumagai, Y.; Sugiura, T.; Andoh, H.; Tsukamoto, T. (AIP Adv., 2020)

(untitled) - Cattaneo, R.; Borodianskyi, E. A.; Kalenyuk, A. A.; Krasnov, V. M. (Phys. Rev. Appl., 2021)

(untitled) - Krasnov, V. M. (Phys. Rev. B, 2010)

(untitled) - Matsubara, I.; Kageyama, H.; Tanigawa, H.; Ogura, T.; Yamashita, H.; Kawai, T. (Jpn. J. Appl. Phys., Part 1, 1989)

(untitled) - Jacobs, T.; Simsek, Y.; Koval, Y.; Müller, P.; Krasnov, V. M. (Phys. Rev. Lett., 2016)

Sapphire. Materials, Manufacturing, Applications - Dobrovinskaya, E. R.; Lytvynov, L. A.; Pishchik, V. (Properties of Sapphire, 2009)

(untitled) - Zavaritsky, N. V.; Samoilov, A. V.; Yurgens, A. A. (Phys. C (Amsterdam, Neth.), 1991)

(untitled) - Crommie, M. F.; Zettl, A. (Phys. Rev. B, 1991)

(untitled) - Ji, M.; Yuan, J.; Gross, B.; Rudau, F.; An, D. Y.; Li, M. Y.; Zhou, X. J.; Huang, Y.; Sun, H. C.; Zhu, Q.; Li, J.; Kinev, N.; et al. (Appl. Phys. Lett., 2014)

(untitled) - Barbara, P.; Cawthorne, A. B.; Shitov, S. V.; Lobb, C. J. (Phys. Rev. Lett., 1999)

(untitled) - Galin, M. A.; Borodianskyi, E. A.; Kurin, V. V.; Shereshevskiy, I. A.; Vdovicheva, N. K.; Krasnov, V. M.; Klushin, A. M. (Phys. Rev. Appl., 2018)

(untitled) - Galin, M. A.; Rudau, F.; Borodianskyi, E. A.; Kurin, V. V.; Koelle, D.; Kleiner, R.; Krasnov, V. M.; Klushin, A. M. (Phys. Rev. Appl., 2020)